Análise do tráfico de drogas no Brasil sob a perspectiva da Teoria Econômica do Crime - Gazzone, Gabriela Casagrande (2022)
This research aims to encourage the discussion about criminal policies intended to confront the drug trafficking. Therefore, the objective is to make use of the valuable studies arising from the Law & Economic theory, notably the part that relates economic principles to the criminal field (Economic Theory of Crime). The pillars of the afore mentioned theory will be analyzed, such as the idea of cost-benefit and human rationality, in favor of a possible modernization of criminal policies to combat trafficking and related crimes. Although in an unfinished way, as it is not intended to exhaust the subject, the research will seek to make use of concrete and recently collected data to stimulate the use of jurimetrics and take more tangible directions that are consistent with the Brazilian reality in this sense